SISTEM PAKAR UNTUK MENDIAGNOSIS PENYAKIT TUMOR OTAK MENGGUNAKAN METODE CERTAINTY FACTOR (CF) - Abdullah Ammar; Sirajudin Hawari; Trevy Jonatya Novella; Ahlijati Nuraminah (JURAL RISET RUMPUN ILMU TEKNIK, 2022)
ABSTRAK The development of computer technology helps many aspects of life. One aspect of life that takes advantage of technological developments is the health sector, in order to solve problems including brain tumors. Brain Tumor Disease is the growth of abnormal cells in or around the brain in an unnatural and uncontrolled manner. Patients with brain tumors continue to increase every year, because the initial symptoms are often underestimated. Therefore created a software that can help diagnose brain tumors using the certainty factor method